Health insurance, a friend in need? Impacts of formal insurance and crowding out of informal insurance - Geng, Xin; Janssens, Wendy; Kramer, Berber; van der List, Marijn (Elsevier, 2018)
Health insurance can improve health-seeking behaviors and protect consumption from health shocks but may also crowd out informal insurance. This paper therefore examines whether impacts of health insurance depend on households’ access to informal insurance, as proxied for by mobile money usage. Based on high-frequency financial diaries data collected in rural Kenya, we find that households with weaker access to informal insurance cope with uninsured health shocks by lowering subsequent non-health expenditures by approximately 25 percent. These same households are able to smooth consumption when health shocks are insured, due to lower out-of-pocket health expenditures. In contrast, households with access to informal insurance are able to smooth consumption even in the absence of formal health insurance. For this latter group, health insurance increases healthcare utilization at formal clinics and does not crowd out gifts and remittances during weeks with health shocks. These findings provide guidance for insurance schemes aiming to target the most vulnerable populations.